Barotropic kinetic energy and enstrophy transfers in the atmosphere. Issue 14 (26th July 2016) - Chemke, R.; Dror, T.; Kaspi, Y.
Abstract: The midlatitude atmosphere is characterized by turbulent eddies that act to produce a depth‐independent (barotropic) mean flow. Using the NCEP (National Centers for Environmental Prediction) Reanalysis 2 data, the latitudinal dependence of barotropic kinetic energy and enstrophy are investigated. Most of the barotropization takes place in the extratropics with a maximum value at midlatitudes, due to the latitudinal variations of the static stability, tropopause height, and sphericity of the planet. Barotropic advection transfers the eddy kinetic energy to the zonal mean flow and thus maintains the barotropic component of the eddy‐driven jet. The classic description of geostrophic turbulence exists only at high latitudes, where the quasi‐geostrophic flow is supercritical to baroclinic instability; the eddy‐eddy interactions carry both the barotropization of eddy kinetic energy upscale to the Rhines scale and the barotropization of eddy potential enstrophy downscale. Key Points: Atmospheric baroclinic to barotropic conversion is localized at midlatitudes and responsible for the barotropization of the eddy‐driven jet The supercriticality affects the latitudinal behavior of eddy‐eddy interactions At high latitudes, eddy‐eddy interactions carry the energy up to the Rhines scale and the enstrophy downscale